(untitled) (Journal of Educational Sciences, 2022)
In the article, the authors present to future social educators an overview of the causes and consequences of adolescents’ predisposition to victim behavior, the nature of this phenomenon as a whole and the history of the emergence of the scientific direction. The main task of a social pedagogue is the social protection of a child, a teenager, providing him with social, psychological or medical assistance, organizing his education, as well as ensuring his rehabilitation and adaptation in society. In general, the social significance of social pedagogy is to help people who are in a difficult, tragic situation - their families, children, helping them to find their place in life, to develop further based on their abilities and abilities. At the same time, in order to solve these problems, the social pedagogue studies the child, determines his condition, the level of isolation and looks for ways out of it, plans.The phenomenon of victimhood will deepen the problem and determine how to understand the psychology of the victim and how to prevent it. The authors also focus on terminological problems of victimology as a scientific direction in the Kazakh language and try to substantiate them. Key words: socio-pedagogical victimology, victimization, victim behavior, "difficult teenagers".